2021
DOI: 10.1140/epjd/s10053-021-00263-9
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent variational dynamics for nonadiabatically coupled nuclear and electronic quantum wavepackets in molecules

Abstract: We propose a methodology to unify electronic and nuclear quantum wavepacket dynamics in molecular processes including nonadiabatic chemical reactions. The canonical and traditional approach in the full quantum treatment both for electrons and nuclei rests on the Born–Oppenheimer fixed nuclei strategy, the total wavefunction of which is described in terms of the Born–Huang expansion. This approach is already realized numerically but only for small molecules with several number of coupled electronic states for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 96 publications
(165 reference statements)
0
2
0
Order By: Relevance
“…New experimental data on the fragmentation of the tyrosine amino acid molecule and the formation of ionised products due to the lowenergy electron impact were presented by Tamuliene et al [5]. Takatsuka [6] has presented a methodology to unify electronic and nuclear quantum wavepacket dynamics in molecular processes including nonadiabatic chemical reactions whereas a R-matrix theory implemented using the pseudostate formalism has been used to calculate elastic and excitation processes in electron interactions with N 2 H and HCO [7]. Suarez-Moreno et al [8] have reported studies on electron interactions with formamide clusters as a model system to understand phenomena relevant to astrophysical, prebiotic and radiobiological processes.…”
Section: New Scientific Insightsmentioning
confidence: 99%
“…New experimental data on the fragmentation of the tyrosine amino acid molecule and the formation of ionised products due to the lowenergy electron impact were presented by Tamuliene et al [5]. Takatsuka [6] has presented a methodology to unify electronic and nuclear quantum wavepacket dynamics in molecular processes including nonadiabatic chemical reactions whereas a R-matrix theory implemented using the pseudostate formalism has been used to calculate elastic and excitation processes in electron interactions with N 2 H and HCO [7]. Suarez-Moreno et al [8] have reported studies on electron interactions with formamide clusters as a model system to understand phenomena relevant to astrophysical, prebiotic and radiobiological processes.…”
Section: New Scientific Insightsmentioning
confidence: 99%
“…Most of theories of nonadiabatic transitions, and those by the Truhlar group as well, rest on the so-called Born–Huang representation [ 37 ], in which time-dependent dynamics of molecules are considered exclusively in the nuclear wave functions, which are supposed to run on the so-called static potential energy hyper-surface (PES) created by time-independent electronic wave functions. Our approach in this paper is, in contrast, based on the time-dependent electronic wave functions, and the nuclear kinematic interactions are taken into account through the coupling of electronic wave-packets [ 38 , 39 , 40 , 41 , 42 ]. In this representation, electron wave-packets induced by photoexcitation are directly tracked in a real-time scale.…”
Section: Introductionmentioning
confidence: 99%